Strychnine poisoning: From air medical transport to pediatric management - Sartorelo Carneiro Bittencourt Almeida, Juliana; Miranda Rodrigues da Cunha, Lara; Cançado Lasmar, Renato; de Paiva Oliveira, Larissa; De Andrade Filho, Adebal; Gonçalves Nogueira, Caio (LAJEC - Latin American Journal of Emergency Care, 2023)
Abstract: Vibration, light and noise are important flight stressors generated by aerospace physiology that directly impact the medical transport of a patient with a Strychnine intoxication, a toxic alkaloid extracted from the seed of Strychnos nux vomica, formerly used as a rodenticide, that was banned in the 90s due to its high lethality. Poisoning by the substance is rare and serious, and its management is complex. Case description: Patient, 2 years and 11 months old, male, admitted to the pediatric emergency department, via air transport, after suspected exogenous strychnine poisoning. The child received supportive treatment, with good response, and was discharged without sequelae. Discussion: This case report a very rare intoxication and correlate it with the need for protective measures for these flight changes, not only to improve teamwork, but primarily to prevent the poor clinical evolution of the victim. In addition, the specifics of the pediatric management of the victim are detailed. Such precautions can be extended to other pathologies that require restriction of noise, stimuli and vibrations. Conclusion: A quick detection, assertive management and measures that reduce stressful situations are essential for a good prognosis in Strychnine intoxication.